Implementation of Learning from Tijan Ad-Darori on the Attributes of Allah and the Prophet to Enhance Students' Character - Aisah, Siti; Hasbullah, Hasbullah; Luthfi, M (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aims to investigate the implementation of Tijan Ad-Darori learning at MTs Darul Amanah Cilayang Cikeusal, Serang Regency, to explore the aspects of Allah's and the Prophet's attributes within the Tijan Ad-Darori book, and to examine how the understanding of these attributes contributes to enhancing students' character development at MTs Darul Amanah Cilayang Cikeusal. The research employs a qualitative descriptive approach, utilizing data collection methods such as observation, documentation, interviews, and literature review. The findings reveal that: 1) Tijan Ad-Darori learning at MTs Darul Amanah Cilayang Cikeusal is conducted through a combination of group and individual reading methods, where students take turns reading aloud while others and the teacher listen, followed by discussions, teacher explanations, and collective recitation according to established guidelines; 2) The Tijan Ad-Darori book addresses the attributes of Allah SWT, covering four domains: Ilahiyat (divine attributes and beliefs in Allah), Nubuwat (relations with the Prophet, messengers, and sacred texts), Ruhaniyat (metaphysical world), and Sam'iyat (knowledge derived from divine sources); 3) The implementation of understanding Allah's attributes and those of the Prophet aims to enhance students' character. This process involves evaluating students' character before and after learning and analyzing the influence and methods used. The results demonstrate that Tijan Ad-Darori learning contributes to forming students' character in alignment with Islamic values.